-3(m-2)=

Simple and best practice solution for -3(m-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(m-2)= equation:


Simplifying
-3(m + -2) = 0

Reorder the terms:
-3(-2 + m) = 0
(-2 * -3 + m * -3) = 0
(6 + -3m) = 0

Solving
6 + -3m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -3m = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -3m = 0 + -6
-3m = 0 + -6

Combine like terms: 0 + -6 = -6
-3m = -6

Divide each side by '-3'.
m = 2

Simplifying
m = 2

See similar equations:

| -74=-7x+4(2x-17) | | 15ab+25ab+-12ab= | | 6a-2ab-8-4ab+3a= | | 11-1/3b=-6 | | 3r^2-13r-10=0 | | 21x-12+3=x-31x | | 8(x+9)-21=0 | | Y=20-16x^2+32x | | 3x^2+15x-8=0 | | x^(1/3)=3 | | 3.6=r(24) | | (4-u)(2u-5)=0 | | 8x^2+4x-3-9x^2= | | 3(5-2x)=3(5x+2) | | 7x-9=5x-53 | | 16x^2-3x-4x^2+5+10= | | 9-4(5x-7)= | | x^2+118x-378=0 | | -6x^2+2+11x^2-13-5x= | | 13-52+f=34 | | 6x-1=3y+2 | | 5(c+9)=5(c-4) | | 2(1/3)x3(2/7) | | r^2-3r=2r+14 | | 2lne+3ln(x-1)=5 | | 5y-3+y+41=6y+40-2 | | 9x^2-14x-4+3x= | | x^-2=9/16 | | 24a/4 | | 19x-3=14+2x | | x^*2=9/16 | | 24a/4= |

Equations solver categories